Turtle splash! : countdown at the pond - Falwell, Cathryn (Greenwillow Books, 2001)
As they are startled by the activities of other nearby creatures, the number of turtles on a log in a pond decreases from ten to one. Includes factual information about the animals mentioned in the story.